Effect of Acidic and Energy Drinks on Surface Roughness of Three Types of Bulk Fill Composite Materials - Linz A. Shalan (College of Dentistry/ University of Baghdad, 2016)
ABSTRACT Background: This study aimed to study the effect of some acidic drinks (Vinegars and fresh Orange juice) and energy drinks (Red bull) on surface roughness of three types of bulkfill composite materials: Filtek posterior bulkfill (3M), Sonicfill (Kerr) and Filtek p60 (3M). Materials and Methods: Total number of 120 samples are prepared by using a mold of (12mm diameter and 3mm height), which were divided into three groups forty samples for each group: Group A: Filtek bulkfill posterior composite (3M), Group B: Sonicfill composite (Kerr), Group C: Filtek P60 (3 M) which then divided into four sub- groups (n=10) (1) samples were kept in distilled water as a control group (2) samples were immersed in Redbull (3) samples were immersed in fresh Orange juice (4) samples were immersed in Vinegars. Immersion of samples were made manually for 5 seconds for 10 cycles at room temperature daily for one month then surface roughness was measured by the use of profilometer ,The data were recorded and statistically analyzed, by the ANOVA and the Tukey test. Results: Data were statistically analyzed using ANOVA and Tukey test which revealed that there were a high significant (p>0.001) increase in surface roughness of the three composite materials after immersion in Vinegar and Redbull drinks after one month with highest value for Filtek Bulkfill posterior composite (3M), than Sonicfill composite (Kerr) and Filtek p 60 (3 M) and there was non-significant difference (p< 0.05) in surface roughness value for the three composite materials after immersion in Fresh orange juice. Conclusions: The effect of energy and acidic drinks depend upon exposure time, composition of the composite material